Changes in Cell Vitality, Phenotype, and Function of Dromedary Camel Leukocytes After Whole Blood Exposure to Heat Stress in vitro - Hussen, Jamal (Frontiers in Veterinary Science, 2021)
The dromedary camel (Camelus dromedarius) is well adapted to the desert environment with the ability to tolerate increased internal body temperatures rising daily to 41–42ºC during extreme hot. This study was undertaken to assess whether in vitro incubation of camel blood at 41ºC, simulating conditions of heat stress, differently alters cell vitality, phenotype, and function of leukocytes, compared to incubation at 37 ºC (normothermia). Using flow cytometry, the cell vitality (necrosis and apoptosis), the expression of several cell markers and adhesion molecules, and the antimicrobial functions of camel leukocytes were analyzed in vitro. The fraction of apoptotic cells within the granulocytes, lymphocytes, and monocytes increased significantly after incubation of camel whole blood at 41°C for 4h. The higher increase in apoptotic granulocytes and monocytes compared to lymphocytes suggests higher resistance of camel lymphocytes to heat stress. In contrast to the reported inhibitory effect of heat stress on the antimicrobial functions of bovine neutrophils, incubation of camel blood at 41°C for 4h enhanced the phagocytosis and ROS production activities of camel neutrophils and monocytes toward S. aureus. Similar to the polarizing effect of heat stress, which has been recently reported for bovine monocytes, monocytes from camel blood at 41°C for 4h significantly decreased their expression level of MHC class II molecules with no change in the abundance of CD163, resulting in a CD163high MHC-IIlow M2-like macrophage phenotype. In addition, heat stress treatment showed an inhibitory effect on the LPS-induced changes in camel monocytes phenotype. Furthermore, in vitro incubation of camel blood at 41°C reduced the expression of the cell adhesion molecules CD18 and CD11a on neutrophils and monocytes. Collectively, the present study identified some heat-stress-induced phenotypic and functional alterations in camel blood leukocytes. The clinical relevance of the heat-stress induced changes in the camel leukocytes for the adaptation of the camel immune response to heat stress conditions needs further in vitro and in vivo studies